2019
DOI: 10.1634/theoncologist.2019-0025
|View full text |Cite
|
Sign up to set email alerts
|

The EMA Review of Mylotarg (Gemtuzumab Ozogamicin) for the Treatment of Acute Myeloid Leukemia

Abstract: On February 22, 2018, the Committee for Medicinal Products for Human Use (CHMP) adopted a positive opinion, recommending the granting of a marketing authorization for the medicinal product gemtuzumab ozogamicin (Mylotarg; Pfizer, New York City, NY), intended for the treatment of acute myeloid leukemia. Mylotarg was designated as an orphan medicinal product on October 18, 2000. The applicant for this medicinal product was Pfizer Limited (marketing authorization now held by Pfizer Europe MA EEIG). The demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…45 Months later, it was approved by the EMA. 46 Side effects, although less serious, are still reported. 40,45…”
Section: Gemtuzumab Ozogamicinmentioning
confidence: 99%
“…45 Months later, it was approved by the EMA. 46 Side effects, although less serious, are still reported. 40,45…”
Section: Gemtuzumab Ozogamicinmentioning
confidence: 99%
“…This led the FDA in 2016 to reapprove GO in adult patients with de novo AML with favorable and intermediate cytogenetics or relapsed leukemia [ 64 ]. In 2018, the EMA reapproved GO combined with daunorubicin and cytarabine for the treatment of patients aged 15 years and above with previously untreated, de novo CD33-positive AML [ 65 ]. GO was subsequently studied in pediatric clinical trials as treatment for de novo and relapsed patients and demonstrated improvements in EFS and relapse rate when combined with chemotherapy in the favorable and intermediate-risk group [ 66 , 67 ].…”
Section: Novel Potential Therapiesmentioning
confidence: 99%
“…In 2017, FDA granted approval of GO with 2 indications: (1) treatment of newly diagnosed CD33-positive AML in adults in combination with DNR and ARA-C at 3 mg/m 2 (up to 5 mg) on days 1, 4, and 7 or as single-agent regimen at 6 mg/m 2 on day 1 and 3 mg/m 2 on Day 8; and (2) treatment of relapsed or refractory CD33-positive AML in adults and in pediatric patients >2 years at 3 mg/m 2 on days 1, 4, and 7 [60,61]. In 2018, EMA approved GO for patients >15 years with previously untreated, de novo CD33-positive AML, at 3 mg/m 2 (up to 5 mg) on days 1, 4, and 7 + DNR 60 mg/m 2 /day on days 1 to 3, and Ara-C 200 mg/m 2 /day by continuous infusion on days 1 to 7 [62,63].…”
Section: Go and Current Indicationsmentioning
confidence: 99%